Distinct Roles of Chromatin Insulator Proteins in Control of the Drosophila Bithorax Complex. Issue 2 (23rd December 2015) - Savitsky, Mikhail; Kim, Maria; Kravchuk, Oksana; Schwartz, Yuri B
Abstract: Chromatin insulators are remarkable regulatory elements that can bring distant genomic sites together and block unscheduled enhancer–promoter communications. Insulators act via associated insulator proteins of two classes: sequence-specific DNA binding factors and "bridging" proteins. The latter are required to mediate interactions between distant insulator elements. Chromatin insulators are critical for correct expression of complex loci; however, their mode of action is poorly understood. Here, we use the Drosophila bithorax complex as a model to investigate the roles of the bridging proteins Cp190 and Mod(mdg4). The bithorax complex consists of three evolutionarily conserved homeotic genes Ubx, abd-A, and Abd-B, which specify anterior–posterior identity of the last thoracic and all abdominal segments of the fly. Looking at effects of CTCF, mod(mdg4), and Cp190 mutations on expression of the bithorax complex genes, we provide the first functional evidence that Mod(mdg4) acts in concert with the DNA binding insulator protein CTCF. We find that Mod(mdg4) and Cp190 are not redundant and may have distinct functional properties. We, for the first time, demonstrate that Cp190 is critical for correct regulation of the bithorax complex and show that Cp190 is required at an exceptionally strong Fub insulator to partition the bithorax complex into two topological domains.